Assessing Energy Budget of Laboratory Fault Slip Using Rotary Shear Experiments and Micro‐Computed Tomography. Issue 1 (17th January 2020) - Zhao, Qi; Glaser, Steven D.; Tisato, Nicola; Grasselli, Giovanni
Abstract: Quantitative assessment of the energy budget of earthquake events is one of the key aspects for understanding the physics of earthquakes. Investigation of laboratory fault slips under controlled conditions can provide insights on this important aspect of the natural and induced earthquakes. We conducted a rotary shear experiment under X‐ray micro‐computed tomography, which allowed in situ and operando measurement of macroscopic stresses and imaging of the newly formed fractures inside the sample. We estimate each component of the energy budget and found that friction energy loss ( E F ), fracture energy ( E G ), and radiated energy ( E R ) account for 70.16%, 15.68%, and 14.15% of the total energy budget, respectively. Quantitative analysis of the micro‐computed tomography images indicates that the energy consumed by creating slip‐induced off‐fault fractures ( E G f ) accounts for only 0.3% of the total energy, less than 2% of the total E G . Key Points: Rotary shear test under micro‐CT measures frictional behavior and shows progressive development of slip induced fractures Fracture surface area estimated by machine learning aided quantitative image analysis Fracture energy accounts for 16% of the total energy budget, among which <2% is consumed by creating off‐fault fractures